Relationship of Parenting Patterns with Toddler Nutritional Status in Palla Public Health Center Southwest Sumba - Mada, Herliana Deliana; Talahatu, Anna Heny; Toy, Sarci Magdalena (Timorese Journal of Public Health, 2021)
One of the factors that play an important role in the nutritional status of children under five is parenting. Parenting is an interaction between children and parents during parenting activities. This study aims to analyze the relationship between maternal parenting and the nutritional status of children under five in the work area of ​​the Palla Health Center, Southwest Sumba Regency. This type of research is analytic observation with a cross-sectional design. The research population is all mothers who have children under five in the work area of ​​the Palla Health Center. The sample size is 88 respondents. Data was collected by using a simple random sampling technique. The results showed that there was a relationship between maternal characteristics (knowledge of maternal nutrition, education, occupation, income), eating patterns, hygiene parenting, and health care patterns with the nutritional status of children under five using the chi-square test where p-value = (0.05) which means that there is a significant relationship between the relationship between maternal parenting and the nutritional status of children under five in the work area of ​​the Palla Public Health Center, Southwest Sumba Regency